Association between insufficient sleep and constipation among elementary school children in Japan - Ritsuko Furuya; Hiroo Wada; Keisuke Onuki; Takayuki Kitazawa; Mariko Miyakawa; Qinye Zhu; Yuito Ueda; Setsuko Sato; Hiroshi Nakano; David Gozal; Takeshi Tanigawa (Sleep and Biological Rhythms, 2025)

Evaluating the effects of climate change on different stages of weathering in some granitic and granodioritic landslide prone areas of Japan - Md. Hasan Imam; Chiaki T. Oguchi; Tsuyoshi Wakatsuki; Mariko Ueda (Modeling Earth Systems and Environment, 2024)

Zircon Trace‐Element Compositions in Cenozoic Granitoids in Japan: Revised Discrimination Diagrams for Zircons in I‐Type, S‐Type, and A‐Type Granites - Yusuke Sawaki; Hisashi Asanuma; Shuhei Sakata; Mariko Abe; Hisahiro Ueda; Wataru Fujisaki; Takeshi Ohno (Island Arc, 2024)
Owing to high resistance to alteration, detrital zircons retain information about their formation ages and parental magmas for a long period of time. Many geochemical researchers have proposed various indicators for zircon to constrain tectonic settings and to identify source rock. Because most detrital zircons analyzed by geochronologic studies are derived primarily from granitoids, we focus on the classification of zircon within granitoids. In the style of alphabetical classification scheme (Igneous, I; Sedimentary, S; and Alkaline, A types), some discrimination diagrams have been proposed. To improve the database and enhance discriminating studies, we examined trace‐element compositions of zircons extracted from some Cenozoic granitoids exposed in the Japan Islands. The zircons showed systematic differences in Nb, Ta, Ce, and P contents. Zircons in Oceanic Arc I‐type granite are poor in Nb and Ta, and these signatures clearly reflect those elements in their parental bodies. Despite their low abundance at the whole‐rock level, zircons in Oceanic Arc I‐type granite are characterized by high Ce content. This is attributable to the relatively oxidizing conditions of Oceanic Arc I‐type magma. Zircons in S‐type granite are characterized by high P and low Ce contents. The former can be explained by high apatite solubility in Al‐rich magma, whereas the reducing environment of S‐type magma is accountable for the latter. The zircon crystallized at the later stage during S‐type granite solidification is slightly depleted in Nb and Ta. This is attributable to the depletion of these elements in the magma by Ti‐bearing minerals such as ilmenite prior to zircon crystallization. In analogy with whole‐rock composition, zircons in transitional I‐A‐type granite have intermediate composition between I‐type and A‐type zircons. On the basis of the updated database, we demonstrated that the Nb/P–Ce/P or Ta/P–Ce/P crossplots are the most useful for discriminating zircons in Oceanic Arc I‐type, I‐type, S‐type, and A‐type granites.

Comprehensive analyses of plant hormones in etiolated pea and maize seedlings grown under microgravity conditions in space: Relevance to the International Space Station experiment “Auxin Transport” - Chiaki Yamazaki; Tomokazu Yamazaki; Mikiko Kojima; Yumiko Takebayashi; Hitoshi Sakakibara; Eiji Uheda; Mariko Oka; Motoshi Kamada; Toru Shimazu; Haruo Kasahara; Hiromi Sano; Tomomi Suzuki; et al. (Life Sciences in Space Research, 2023)

Assessment of climate-induced degree of chemical weathering in some granite and granodiorite slopes of Japan - Md. Hasan Imam; Chiaki T. Oguchi; Tsuyoshi Wakatsuki; Mariko Ueda (Modeling Earth Systems and Environment, 2019)

Regulation of asymmetric polar auxin transport by PsPIN1 in endodermal tissues of etiolated Pisum sativum epicotyls: focus on immunohistochemical analyses - Motoshi Kamada; Kensuke Miyamoto; Mariko Oka; Junichi Ueda; Akira Higashibata (Journal of Plant Research, 2018)

The concentration of iodine in horse serum and its relationship with thyroxin concentration by geological difference - Mariko Mochizuki; Noriyuki Hayakawa; Fumiko Minowa; Akihiro Saito; Katsumi Ishioka; Fukiko Ueda; Kimihiro Okubo; Hiroyuki Tazaki (Environmental Monitoring and Assessment, 2016)

Functional analyses of the plant-specific C-terminal region of VPS9a: the activating factor for RAB5 in Arabidopsis thaliana - Mariko Sunada; Tatsuaki Goh; Takashi Ueda; Akihiko Nakano (Journal of Plant Research, 2016)

Changes in metabolism of cell wall polysaccharides in oat leaves during senescence: relevance to the senescence-promoting effect of methyl jasmonate - Kensuke Miyamoto; Mariko Oka; Eiji Uheda; Junichi Ueda (Acta Physiologiae Plantarum, 2013)

Interaction Between Titanium and Cadmium in Various Guinea Pig Organs - Takashi Takano; Takeharu Kaneda; Masaki Kaneshige; Tomoko Tsutsumi; Yoshitsugu Ochiai; Kazumasa Shimizu; Ryo Hondo; Mariko Mochizuki; Fukiko Ueda (Biological Trace Element Research, 2013)

Investigation of Cadmium Contamination Using Hair of the Japanese Macaque, Macaca fuscata, from Shimokita Peninsula, Aomori Prefecture in Japan - Mariko Mochizuki; Reiko Anahara; Tomoki Mano; Yuri Nakayama; Mutsumi Kobori; Toshinori Omi; Shiro Matsuoka; Fukiko Ueda (Bulletin of Environmental Contamination and Toxicology, 2012)

The Distribution of Several Elements in Cat Urine and the Relation Between the Content of Elements and Urolithiasis - Mariko Mochizuki; Misato Morikawa; Takuya Yogo; Kimiyo Urano; Katsumi Ishioka; Minoru Kishi; Ryo Hondo; Fukiko Ueda; Toshinori Sako; Fujiro Sakurai; Norio Yumoto; Masahiro Tagawa (Biological Trace Element Research, 2011)

A Basic Study on the Biological Monitoring for Vanadium—Effects of Vanadium on Vero Cells and the Evaluation of Intracellular Vanadium Contents - Mariko Mochizuki; Eiko Kudo; Mitsuho Kikuchi; Takashi Takano; Yojiro Taniuchi; Tomoya Kitamura; Ryo Hondo; Fukiko Ueda (Biological Trace Element Research, 2011)

A new index for evaluation of cadmium pollution in birds and mammals - Mariko Mochizuki; Makoto Mori; Ryo Hondo; Fukiko Ueda (Environmental Monitoring and Assessment, 2008)

The Distribution of Molybdenum in the Tissues of Wild Ducks - Mariko Mochizuki; Rei Sasaki; Yuko Yamashita; Mayumi Akinaga; Nana Anan; Sakura Sasaki; Ryo Hondo; Fukiko Ueda (Environmental Monitoring and Assessment, 2002)

Cadmium Contamination in Wild Birds as an Indicator of Environmental Pollution - Mariko Mochizuki; Ryo Hondo; Kiichi Kumon; Rei Sasaki; Hironori Matsuba; Fukiko Ueda (Environmental Monitoring and Assessment, 2002)

Establishment of Bone Marrow-Derived Endothelial Cell Lines From ts-SV40 T-antigen Gene Transgenic Rats - Kenji Hattori; Mariko Muta; Masakazu Toi; Hisashi Iizasa; Machiko Shinsei; Tetsuya Terasaki; Masuo Obinata; Masatsugu Ueda; Emi Nakashima (Pharmaceutical Research, 2001)

Activities of auxin polar transport in inflorescence axes of flower mutants ofArabidopsis thaliana: Relevance to flower formation and growth - Mariko Oka; Junichi Ueda; Kensuke Miyamoto; Kiyotaka Okada (Journal of Plant Research, 1998)